First evidence of Hadrosauropodus in Gondwana (Yacoraite Formation, Maastrichtian-Danian), northwestern Argentina - Díaz Martínez, Ignacio; de Valais, Silvina; Cónsole Gonella, Carlos Alfredo (Journal of African Earth Sciences)
Uppermost Cretaceous (Campanian-Maastrichtian) large ornithopod tracks are scarce in Gondwana. This record is limited to few citations in the northern Argentina, Peru and possibly Bolivia, although their ichnological affinities are still under discussion. Recently, a new vertebrate tracksite with large ornithopod tracks has been found in the Maimará locality, Jujuy province, Argentina, from the Yacoraite Formation (Maastrichtian-Danian). The best preserved track is characterized by having large and bilobed heel impression and wide and short digit impressions with blunt claw marks. This record represents the unambiguous record of large ornithopod tracks in Gondwana in the Uppermost Cretaceous, and its features allow classifying it as Hadrosauropodus. Previously, this ichnotaxon had exclusively Laurasian distribution. Therefore, this record is the first evidence of Hadrosauropodus from Gondwana expanding the geographic range of this ichnogenus. A member of Hadrosauridae is reinforced as possible trackmaker of the Hadrosauropodus tracks. Uppermost Cretaceous hadrosaurid dinosaurs are scarce in Gondwana, being the record limited to Patagonia, La Pampa province and Antarctica. Therefore, the Maimará tracks increase the knowledge of this kind of dinosaur from Gondwana. Fil: Díaz Martínez, Ignacio. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigación en Paleobiología y Geología; Argentina Fil: de Valais, Silvina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigación en Paleobiología y Geología; Argentina Fil: Cónsole Gonella, Carlos Alfredo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Tucumán. Instituto Superior de Correlación Geológica. Universidad Nacional de Tucumán. Facultad de Ciencias Naturales e Instituto Miguel Lillo. Departamento de Geología. Cátedra Geología Estructural. ...